PARADIGMATIC SOUND INTERFERENCE IN THE ENGLISH SPEECH OF TURKOPHONES - Satibaldiyev, Erkinjon (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
This study explores language interference in Turkophone speakers learning English, emphasizing the impact of phonetic and phonological discrepancies on second language acquisition. It highlights the need for a nuanced teaching approach that incorporates phonetic training and practical language application to address the unique challenges faced by learners from linguistically diverse backgrounds.